Boundary spanning and isomorphism interactions - Symeon Mandrinos; Constance Liew Sat Lin (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2024)
This study explores the relationship between isomorphism, boundary-spanning, institutional restrictions, and procedural congruence. Using fuzzy (set-theoretic) logic and concepts of causal dependence, we aim to clarify the presence of isomorphism on firms designated as protected origins and boundary-spanning. Employing fuzzy (settheoretic) logic, we analyse the interactions between isomorphism, institutional restrictions, procedural congruence, and boundary-spanning. By investigating causal dependencies, we uncover the underlying mechanisms shaping firms’ interactions within diverse contexts. Our study reveals that isomorphism interactions can be examined through causal (counterfactual) dependence, emphasising their significance. Furthermore, causal dependence can occur without explicit causation, indicating a transitive relationship involving interactions. Isomorphism can serve as a counterexample to causal dependence, maintaining a boundary interaction between contextual factors and institutional constraints. Additionally, causal dependence involving interactions may not necessarily constrain isomorphism, suggesting an intransitive relationship. Isomorphism may also present a facade of conformity when analysed through causal (counterfactual) dependence, highlighting the complexity of these interactions. This research contributes to the literature by examining the relationship between isomorphism and institutional constraints, providing original insights into boundary-spanning and isomorphism. Moreover, our study advances understanding of causal dependence in explaining firm interactions, with implications for international business.